2019
DOI: 10.1103/physrevb.99.241402
|View full text |Cite
|
Sign up to set email alerts
|

High-angle optically accessible Brewster cavity exciton-polaritons

Abstract: We report on the observation of the strong-coupling regime between quantum well excitons and a high incidence "Brewster cavity mode" previously identified as the generalized Brewster angle condition in multilayer structures [H. F. Mahlein, J. Opt. Soc. Am. 64, 647 (1974)]. This propagating mode is inside the light cone and therefore can be accessed from the top side of the sample without the need for prism or grating coupling methods. The observed anticrossing is clear evidence of the strong light-matter coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Dielectric with refractive index of 1.41 and sector angle about of 90 degree used in simulations 28 . Simulations have shown that the greatest beam curvature can be obtained when the remote segment is irradiated near the Brewster angle 30 .…”
Section: Double Photonic Hookmentioning
confidence: 99%
“…Dielectric with refractive index of 1.41 and sector angle about of 90 degree used in simulations 28 . Simulations have shown that the greatest beam curvature can be obtained when the remote segment is irradiated near the Brewster angle 30 .…”
Section: Double Photonic Hookmentioning
confidence: 99%
“…Dielectric with refractive index of 1.41 and sector angle about of 90 degree used in simulations 28 . Simulations have shown that the greatest beam curvature can be obtained when the remote segment is irradiated near the Brewster angle 30 . Combining key parameters of the photonic hook, and having in mind the quality criteria for the photonic jet 31 , we propose to characterize the PH by a quality criterion Q as…”
Section: Double Photonic Hookmentioning
confidence: 99%